Napoleon's last island : a novel - Keneally, Thomas (Atria Books, 2016)
A "historical novel set on the remote island of Saint Helena about the remarkable friendship between a young woman and one of history's most intriguing figures, Napoleon Bonaparte, during the final years of his life in exile."--